RESERVE LINES OF PARALLEL TRAINING IN THE FORMATION OF PROFESSIONAL READINESS OF HIGHER SCHOOL STUDENTS - Kulaeva, Zalina (European Science, 2022)
The system analysis of the learning process considers the problem of activating the activity of students in the educational process through programming, control of independent work and the creation of motivation through the professional specialization of